2022
DOI: 10.1186/s12877-022-03259-1
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of retirement satisfaction in the older adults of Urmia: a cross-sectional study

Abstract: Background Retirement is a challenge that, as a process, influences the individual’s role, status, life patterns, expectations, and available resources. Therefore, the present study aims at determining the predictors of retirement satisfaction among men in the city of Urmia. Methods In this descriptive-analytical study, 140 retired men living in Urmia were selected by multi-stage sampling method. The instruments used are the Retirement Satisfaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The ability to successfully implement retirement plans is directly related to retirement satisfaction [15]. Honarvar et al in their research showed that satisfaction with retirement is related to the assessment of the quality of life and life satisfaction [16]. In their own research, the moment of retirement was assessed by seniors as a change for the better in their lives, both in the group of seniors participating in the UTA classes and in the group of seniors not participating in them.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to successfully implement retirement plans is directly related to retirement satisfaction [15]. Honarvar et al in their research showed that satisfaction with retirement is related to the assessment of the quality of life and life satisfaction [16]. In their own research, the moment of retirement was assessed by seniors as a change for the better in their lives, both in the group of seniors participating in the UTA classes and in the group of seniors not participating in them.…”
Section: Discussionmentioning
confidence: 99%